A relativização do absoluto: o enunciado como unidade real da comunicação verbal no discurso jurídico-judicial pelo prisma do Círculo de Bakhtin - (:unkn) unknown (Universidade Federal de Goiás, 2019)
It is a Dissertation that files the main reflections of a research whose corpus covers the production conditions of the multiple discursive materialities originated from the legal-judicial discourse analysis, in particular on the relativization of the legal prohibition of the university professor salary garnishment through judicial decisions of the Goiás’ state Judiciary Power: one in the first instance (Judge of Law), at the Public Prosecutor's Office request, in a Execution process of the debt contracted to the Municipal Executive Power; the other in two appeals filed before the Goiás’s State Justice Court, in the frustrated attempt to cancel the illegitimate garnishment of 30% (thirty percent) of the salary perceived by the aforementioned federal public education professor to satisfy debts that had no nature of human rights protection argument that in order to adopt judicial measures there was no coherence between the legal-judicial discourse and the production / interpretation / application of the Normative Texts statements that regulate the subject, especially on the fact that the law , at the time, ensure the absolute garnishment of wages and the counterparts. Other decisions were also part of the materialities involved in the discursive event that is this research object, due to the need for a broader approach to legal-judicial discourse in the proposed terms. For this, the Materialist Dialectic method was used under the privileged focus of the Bakhtin Circle's Dialogical view, which, although it did not specifically, on the discursive production examination in the juridical arena, offers, by means of his Philosophical-scientific contributions to the language studies, in particular by the concepts of: concrete utterances and ideological sign (by us appropriated as categories of analysis), the basis for understanding the contradictions underlying the Legal-Judicial Discourse, emphasizing the vicissitudes of an interpretive system in a linguistic community, whose conclusions directly impact property, freedom and the life of the people, as well as its reflections in the juridical arena, especially in the scope of human rights, revealing, as a background, the legal ideologies involved in such dialectical / dialogical process.
The relativization of the absolute: the concrete utterances as a real unit of verbal communication in the legal-judicial discourse through the prism of the Bakhtin Circle
Keywords: Discurso jurídico-judicial; Círculo de Bakhtin; Enunciado concreto; Signo ideológico; Legal-judicial discourse; Concrete utterances; Ideological sign; Bakhtin circle; LINGUISTICA, LETRAS E ARTES::LINGUISTICA